107 A mixed-reality holographic viewing platform enabling interaction with 3D electroanatomical maps using the hololens. (4th June 2021) - Malaweera, Anura; Jogi, Ramit; Wright, Matthew; O'Neill, Mark; Williams, Steven
Abstract : Introduction: Three dimensional (3D) electroanatomical maps (EAMs) created during electrophysiology procedures are traditionally displayed on 2D monitors connected to mapping systems. This has limitations, such as the lack of interaction with EAMs, the need for another user to control them, and the size of EAM displayed, which is limited by the resolution of these monitors. To overcome these, we created a novel technology to display EAMs on a mixed reality (MR) platform. Methods: We used the Microsoft® HoloLens to create this MR platform. Studies from patients who had already undergone catheter ablation for atrial fibrillation, where EAMs of the left atria had been generated using different mapping systems (CARTO®, Rhythmia™ and EnSite Precision™) were utilised. These EAMs consisting of 3D coordinates and annotations (e.g. voltage & activation times) were exported from the mapping system. EAMs were then compiled and transferred to the HoloLens using custom-developed functions on Unity©, Microsoft® C# and VisualStudio. Subsequently, feedback was obtained from 3 independent electrophysiologists on this technology. Results: We successfully exported the EAMs generated on CARTO®, Rhythmia™ and EnSite Precision™ mapping systems as holograms on to the HoloLens (Figure). Positive feedback included themes such as 1) the ability to use hand gestures and voice commands to interact with EAMs independent of another user unlike traditional cardiac mapping systems 2) offering an interactive 3D holographic experience whilst preserving the operators' physical interaction in the cardiac catheter lab 3) the capacity to better appreciate 3D geometry of EAMs in comparison to 2D monitors. The challenge of wearing a headset during long procedures was perceived as a disadvantage. Conclusion: This technology, which can be used with any mapping system, is currently optimised for offline display. Our software will be made available as an opensource teaching and simulation tool (at www.Openep.io). Users will be able to explore EAMs for research, planning complex cases and immersive learning. The future directions will include extending this toolkit for real-time cardiac mapping with catheter localisation, and could potentially be translated to other cardiac imaging modalities. Conflict of Interest: None